MOTIF KELUARGA DALAM MEMILIH PELAYANAN KESEHATAN BAGI ORANG LANSIA PADA MASA PANDEMI COVID-19 - Billah S, May Salwa (Paradigma, 2022)
Elderly people are a group of people who are 60 years old or more. As the age of the elderly, it will experience a decline in him. So that the elderly are considered helpless and have no role in choosing health services for themselves. Through this, the family has an important role in choosing health services for the elderly. In choosing health services for the elderly, there is a motive in the family. The purpose of this study was to analyze family motives in choosing health services for the elderly during the COVID-19 pandemic. Researchers used Alfred Schutz’s phenomenological perspective, to see family motives in choosing health services for the elderly. The method used in this research is a qualitative approach. The results showed that there were 5 health services chosen by the family, namely village health centers, central health centers, doctors’ practices in Beru Village, traditional medicine and hospitals. In choosing health services for the elderly, there is a motive in the family. The motives of each family in choosing health services for the elderly are different. This happens because of differences in family views about the health of the elderly, the family’s economic situation, education owned by the family and the condition of the elderly. Keywords : Family Motives; Elderly People; Covid-19 Pandemic; Health Services.